Further insights into the discoloration of TATB under ionizing radiation. Issue 3 (2nd July 2020) - Lewis, Dan; Padfield, James; Connors, Scott; Wilson, Ian; Akhavan, Jacqueline
ABSTRACT: To determine degradation products formed by exposure of TATB to ionizing radiation, a computational and experimental study is presented. Thermochemical and spectral data have been calculated using DFT at the MH06-HF/aug-cc-pVTZ level which suggest the formation of the cation radical derivative of TATB. Irradiated TATB samples showed the widely reported yellow-to-green discoloration, with measured CIE L*, a*, b* and RGB values correlating with total dose. Trace quantities of a mono-furazan derivative were detected by HPLC-MS; the discoloration is not attributed to this, but rather to the presence of a paramagnetic species (i.e., the cation), as detected by ESR measurements. Recrystallized irradiated TATB samples reverted to their original color, further suggesting it is the cation radical that is responsible for color change.